KONTRIBUSI PENGAWAS SEKOLAH TERHADAP PEMENUHAN STANDAR NASIONAL PENDIDIKAN DI SMA NEGERI 1 UNGGULAN KOTA TERNATE - Sasmito, Muhammad Asdar (Universitas Negeri Makassar, 2017)
The objectives of the research are to examine (i) the contribution of school supervisors to fullfill National Education Standar in SMA Negeri 1 Unggulan Kota Ternate from managerial supervison aspect, (ii) the contribution of school supervisors to fullfill National Education Standard in SMA Negeri 1 Unggulan Kota Ternate from academic supervison aspect (iii) the contribution of school supervisors to fullfill National Education Standard in SMA Negeri 1 Unggulan Kota Ternate from the evaluation of implementation of managerial supervison aspect and academic supervison aspect.This research using qualitative approach with 4 informants from school supervisors, 1 headmaster, 3 vice headmasters, 1 head officer, and 4 teachers. Data were collected through two steps, the first was interview and the second was observation. The result of the research showed that (i) the contribution of school supervisors in managerial supervison aspect in the form of guidance about the educator standard and officer education standard, the passive and active equipment standard, the managerial standard, and the cost standard were provided to headmaster, vice headmasters, and head officer. (ii) the contribution of school supervisors in academic supervison aspect in the form of guidance about the content standard, the process standard, the graduation competence standard, and evaluation standard were provided to the teachers. (iii) the contribution of active participation school supervisors in evaluation aspect in the form of active participation to evaluate the implementation of managerial supervison aspect and academic supervison aspect.